The larvae of Micropterna coiffaiti Décamps 1963, Micropterna taurica Martynov 1917, and Potamophylax goulandriorum Malicky 1974 (Trichoptera: Limnephilidae), including a key to the hitherto known Stenophylacini larvae of the Hellenic western Balkan region - Waringer, Johann; Malicky, Hans (Zootaxa, 2016)
The paper gives a description of the hitherto unknown larvae of Micropterna coiffaiti, Micropterna taurica, and Potamophylax goulandriorum (Trichoptera: Limnephilidae). Information on the morphology of the larvae is given and the most important diagnostic features are illustrated. In the context of published keys, the larva of Micropterna coiffaiti keys together with Micropterna sequax, Stenophylax mitis, and Stenophylax permistus. Species can be easily diagnosed by presence/absence and the structure of posterior sclerites at the lateral protuberances, by the extent of head spinule fields, and by the number of posterolateral setae on abdominal dorsum IX. Micropterna taurica keys together with Micropterna nycterobia. This pair can be separated by the setae posterior of the dorsal protuberance which are lacking in M. nycterobia but present in M. taurica. Finally, Potamophylax goulandriorum keys together with P. cingulatus, P. latipennis, and P. luctuosus. Currently it is not possible to separate this species quartet morphologically. With respect to distribution, M. coiffaiti which has been reported from the Eastern Aegean islands in Greece, the Levant, Turkey, and Cyprus, whereas M. taurica ranges from Bulgaria and Greece (Crete, Karpathos, mainland Greece) to Cyprus and Turkey. Potamophylax goulandriorum is known from mainland Greece and Macedonia only. In addition, ecological characteristics are briefly discussed, and a key to the hitherto known Stenophylacini larvae of European Ecoregion 6 (= Hellenic western Balkan region) is included.